Impact of green logistics on Vietnam's regional trade - Mai Ngoc Tran (Asian Journal of Shipping and Logistics (AJSL), 2024)
This study investigates the impact of green logistics on Vietnam's regional trade within the frameworks of the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), Regional Comprehensive Economic Partnership (RCEP), Association of Southeast Asian Nations (ASEAN), and Asia-Pacific Economic Cooperation (APEC) from 2007 to 2020. Employing a newly formulated Green Logistics Performance Index (GLPI) derived through Principal Component Analysis (PCA), the research assesses how sustainable logistics practices influence trade performance. An extended gravity model is utilized to analyze the impact of green logistics across different regional trade agreements. The findings suggest that improved green logistics correlate positively with enhanced trade outcomes, highlighting the dual benefits of sustainability efforts in the environmental and economic realms. The study contributes to the limited empirical research on the intersection of green logistics and trade in Vietnam, offering a methodological approach for future analyses in this field. It provides valuable insights for businesses and policymakers aiming to align economic growth with sustainability objectives.
Keywords: F14; F18; Q56; 650; Green logistics; Trade performance; Vietnam; Regional trade agreements; Green logistics performance index (GLPI); Principal component analysis (PCA); Sustainability; CPTPP; RCEP; ASEAN; APEC